The expression of ferroptosis-related proteins GPX4 and PTGS2 in colonic tissues of pediatric Crohn’s disease - Shuanghong Zhang; Chunzhi Kang; Xiaoxiao He; Hui Huang; Qian Xiao (Jornal de Pediatria)
Objective: To investigate the expression of ferroptosis-related proteins GPX4 and PTGS2 in pediatric Crohn’s disease (CD). Methods: Pediatric CD colonic tissues by colonoscopy biopsy were selected as the subjects. The Pediatric Crohn’s Disease Activity Index (PCDAI) was used to assess the disease activity of CD. Immunohistochemistry was used to detect the expression of GPX4 and PTGS2. Results: 30 CD cases were collected, with an average age of 12.36±2.65 years, including 9 in the mild activity phase, 8 in the moderate activity phase, and 13 in the severe activity phase. The positive expression rate of GPX4 in CD colonic tissues was lower than that in normal colonic tissues (p = 0.02); PTGS2 in CD colonic tissues was higher than that in normal colonic tissues (p = 0.004). Based on the average optical density (AOD) values of the positive reactants, the relative expression levels of GPX4 in CD colonic tissues were lower than those in normal colonic tissues (p = 0.02); PTGS2 in CD colonic tissues were higher than those in normal colonic tissues (p = 0.000). The staining scores of GPX4 decreased with increasing CD disease activity (p < 0.001); PTGS2 increased with increasing CD disease activity (p < 0.001). GPX4 was negatively correlated with CD disease activity (r = −0.326); PTGS2 was positively correlated with CD disease activity (r = 0.299). Conclusion: GPX4 and PTGS2 may be involved in the process of ferroptosis in CD intestinal epithelial cells and are correlated with the severity of pediatric CD.